Pakistan - Klepeis, Alicia, 1971- (2020)
"Engaging images accompany information about Pakistan. The combination of high-interest subject matter and narrative text is intended for students in grades 3 through 8"--Provided by publisher.
Deosai National Park -- Location -- Landscape and climate -- Wildlife -- People -- Communities -- Customs -- School and work -- Play -- Food -- Celebrations -- Timeline -- Pakistan facts -- Glossary -- To learn more.
Includes bibliographical references (page 31) and index.
Grades 3-8.
Ages 7-13.
Keywords: Pakistan -- Juvenile literature; Pakistan -- Social life and customs -- Juvenile literature